Pengaruh Pembelajaran Daring terhadap Mental Healthy Mahasiswa Jurusan Akuntansi - Salsabila, Safitri; Syarif, Vandi Andiono; Rahmah, Ziyan Maulida; Nagari, Primasa Minerva (JPAK : Jurnal Pendidikan Akuntansi dan Keuangan, 2021)
The Corona Virus (Covid-19) pandemic is still ongoing from the beginning of March until now in Indonesia, seeing this the government immediately issued new policies such as carrying out activities at home for students from Early Childhood Education to Higher Education levels. The government does not recommend face-to-face learning (offline) and is replaced with online learning that can be done at home. This study aims to determine how much influence online learning has on the mental healthy of students majoring in accounting who are studying at the State University of Malang. The author conducted a study entitled "The Effect of Online Learning on Mental Healthy Students of the Accounting Department". This type of research uses a qualitative research type with a phenomenological approach. Using qualitative research in order to obtain accurate information or data in knowing the effect of online learning on students majoring in accounting at the State University of Malang and using data collection techniques through filling out questionnaires through google forms given to accounting students. The results of this study indicate that students during online learning experience difficulties in receiving the material presented and experience stress due to thinking about the workload given so that it is difficult to sleep. Therefore, it is necessary to have self-motivation to be more active in participating in learning even though online, besides being able to manage time better so that the tasks given are quickly completed and no longer a burden.